2022
DOI: 10.1371/journal.pone.0263600
|View full text |Cite
|
Sign up to set email alerts
|

Current ionising radiation doses in the Chernobyl Exclusion Zone do not directly impact on soil biological activity

Abstract: Although soil organisms are essential for ecosystem function, the impacts of radiation on soil biological activity at highly contaminated sites has been relatively poorly studied. In April-May 2016, we conducted the first largescale deployment of bait lamina to estimate soil organism (largely soil invertebrate) feeding activity in situ at study plots in the Chernobyl Exclusion Zone (CEZ). Across our 53 study plots, estimated weighted absorbed dose rates to soil organisms ranged from 0.7 μGy h-1 to 1753 μGy h-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Although the Red Forest has slowly been recolonised by less radiosensitive deciduous tree species and understorey vegetation, it has poor habitat quality. In a recent paper (Beresford et al, 2022), we report that soil biological activity (invertebrates) is comparatively low in the Red Forest and suggest that this may be a residual consequence of the acute high exposure the ecosystem experience in 1986. We recognised that studies will continue to use the Red Forest as a study site because of the high dose rates organisms receive there.…”
Section: Con S Ider Ati On S On S Tud Ie S In R Adiolog Ic Ally Conta...mentioning
confidence: 87%
“…Although the Red Forest has slowly been recolonised by less radiosensitive deciduous tree species and understorey vegetation, it has poor habitat quality. In a recent paper (Beresford et al, 2022), we report that soil biological activity (invertebrates) is comparatively low in the Red Forest and suggest that this may be a residual consequence of the acute high exposure the ecosystem experience in 1986. We recognised that studies will continue to use the Red Forest as a study site because of the high dose rates organisms receive there.…”
Section: Con S Ider Ati On S On S Tud Ie S In R Adiolog Ic Ally Conta...mentioning
confidence: 87%
“…In the 2000s, research methods and technology drastically improved as metagenomic analysis emerged to address a large number of output data [70,71]. Regarding abundance, Beresford et al (2022) [72] measured the feeding activity of soil fauna via the bait-lamina strip test and demonstrated that biological activity was low in "the Red Forest" in the 10 km zone of the Chernobyl NPP, in 2016, due to a residual effect of acute exposure just after the accident. This finding is consistent with that of Mousseau et al (2014) [73], which showed that leaf litter mass loss was 40% lower at the most contaminated site within 30 km of the Chernobyl NPP in 2007 than at the site with a normal background radiation level.…”
Section: Chernobyl Studiesmentioning
confidence: 99%
“…An important direction in this research area is also to understand why some wild species do not seem to be able to adjust their life‐history traits when living in environments that have become highly mutagenic. This is the case, for example, of the crustacean Asellus aquaticus that live in the Chernobyl region: according to Robertson and Blumstein ( 2019 ), the current dose rates at Chernobyl are not causing discernible effects on the reproductive output of A. aquaticus (see Fuller et al., 2018 and also Beresford et al., 2022 ; Burraco et al., 2021 ). It remains uncertain whether this species possessed robust preexisting anti‐cancer defences, enabling it to mitigate the impacts of harmful radiation, thus showing no effect on life history traits.…”
Section: Introductionmentioning
confidence: 99%